PENGARUH GAYA MENGAJAR GURU DAN KEBIASAAN BELAJAR TERHADAP HASIL BELAJAR (Studi Pada Mata Pelajaran IPS Peserta Didik Di SMP Negeri Satu Atap Plakpak Kecamatan Pegantenan Kabupaten Pamekasan) - Djauhari, Achmad (Jurnal Penelitian dan Pendidikan IPS, 2017)
The objective of this research was to found scientific information whether there was significant effect of TeacherÃ¢â‚¬â„¢s Teaching Styles toward studentsÃ¢â‚¬â„¢ learning outcomes whether there was significant effect of studentsÃ¢â‚¬â„¢ learning habits toward studentsÃ¢â‚¬â„¢ learning outcomes and whether there was significant effect of TeacherÃ¢â‚¬â„¢s Teaching Styles and studentsÃ¢â‚¬â„¢ learning habits simultaniousely toward studentsÃ¢â‚¬â„¢ learning outcomes of social science subject at Stat Unior High School Satu Atap Plakpak of Pegantenan District in Pamekasan Regency Metode used of this research are questionnaire and documentation of TeacherÃ¢â‚¬â„¢s Teaching Styles that was arranged to get data about social economy status, this questionnaire was consisted of sixteen questions studentsÃ¢â‚¬â„¢ learning habits questionnaire was arranged to get studentsÃ¢â‚¬â„¢ learning habits, this questionnaire consisted of seventeen questions. While documentation was taken from report score ofÃ‚Â State Junior High School Satu Atap Plakpak Pegantenan District Pamekasan Regency in 2016-2017 academic year. On the basis of evidence and analysis result of TeacherÃ¢â‚¬â„¢s Teaching Styles data with correlation coefficient 0,133 signification level 5% and probability 0.000. because probability smaller than 0,05 thus studentsÃ¢â‚¬â„¢ habitual learning hypothesis had significant effect toward studentsÃ¢â‚¬â„¢ learning outcomes while correlation index 0,113 and signification level 0,5% with probability 0,000. Because probability smaller than 0,05 thus studentsÃ¢â‚¬â„¢ learning habits hypothesis had significant effect toward studentsÃ¢â‚¬â„¢ learning outcomes, while the result of multy regression showed that R-acount 0,39 and R table 0,125. Because R-acount bigger than R-table thus TeacherÃ¢â‚¬â„¢s Teaching Styles and studentsÃ¢â‚¬â„¢ learning habits had significant effect toward studentsÃ¢â‚¬â„¢ learning outcomes and if it tested using F-account 5,929 and signification level 5% with probability 0,007 if F-table compared with documentation 37-1 = 36 found a number 0,133. because probability bigger than 0,05 and F-acount bigger than F-table thus TeacherÃ¢â‚¬â„¢s Teaching Styles and studentsÃ¢â‚¬â„¢ learning habits hypothesis had significant effect collectively toward studentsÃ¢â‚¬â„¢ learning outcomes of social science subject at Satu Atap Plakpak of Pegantenan Distrik in Pamekasan Regency.